Application of a novel 50K SNP genotyping array to assess the genetic diversity and linkage disequilibrium in a farmed Pacific white shrimp (Litopenaeus vannamei) population - Garcia, Baltasar F. [UNESP]; Bonaguro, Álvaro; Araya, Carolina; Carvalheiro, Roberto [UNESP]; Yáñez, José M. (Elsevier, 2021)
The inclusion of genomic information became a reality in shrimp breeding and it is expected to accelerate the genetic gain over time. The decay of linkage disequilibrium (LD) between single nucleotide polymorphisms (SNPs) is an important measure to evaluate the feasibility of implementing genomic selection. The aim of this study was to evaluate the use of a novel 50 K SNP array tool to characterize the genomic diversity, LD and effective population size (Ne) in a farmed shrimp population. A total of 96 animals (40 sires and 56 dams) were genotyped using the novel Illumina AquaArray HD (50 K) vannamei®. Quality control (QC) of genomic data was performed and three different minor allele frequency (MAF) exclusion thresholds were applied: < 0.10 (QC1), < 0.05 (QC2) and < 0.01 (QC3). After QC, 34,425, 39,091 and 42,789 SNPs were retained for QC1, QC2 and QC3, respectively, validating the high informativeness of this SNP array to this particular shrimp breeding population. The population showed a considerable high overall heterozygosity in comparison to other aquaculture species meaning that genetic diversity is stable despite selection. The principal component analysis revealed three genetically distant groups with the first two principal components explaining 27.7 % of total variation. LD decayed rapidly in the first 30Kb of distance between markers from 0.20 to 0.07 and then decreased to 0.02 in the long-range distance. These results suggest a relatively recent incorporation of animals from different populations in the broodstock. Ne size reduced from 7,871 to 301 animals in 827 generations for QC1, 8,253 to 305 animals for QC2 and 8,957 to 315 animals for QC3, both in 899 generations. Contemporary Ne was close to 86 for all QCs. The level of LD estimated suggests that genomic selection and genome-wide association studies are feasible in shrimp by using this SNP array.
Keywords: Effective population size; Linkage disequilibrium; Shrimp; SNP array